IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TOKO CELULER TERBAIK DENGAN METODE TOPSIS BERBASIS WEB - Ahmad Saefudin; Munawaroh (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In this all-electronic era, gadget users, especially mobile phones, are increasingly mushrooming. This is certainly a great opportunity for mobile phone sellers to make a profit. Due to the high consumer demand for these cellphones, now there are many shops that sell these devices, ranging from cellphones with simple features to even sophisticated ones. This is of course a separate task for mobile phone sellers to serve buyers well and effectively. The number of cellphone shops that sell various kinds of cellphone products, makes the store must improve the quality of service so that consumers are interested in buying cellphone products at the store. With this the author makes a decision support system for selecting the best Cellular store with the Web-based TOPSIS method built using PHP as Server Side Programming Language, MySQL as the database server.